Quality features of university information environment in its external indicators. (2016) - Noskova, Tatiana; Pavlova, Tatiana; Yakovleva, Olga; Morze, Nataliia; Drlík, Martin
The paper represents the preliminary results of the ongoing comparative study of information environments in the frame of the European project 'IRNet'. The aim of this study is to substantiate and verify a set of external indicators for the virtual educational environment of the University, which allows to determine its quality and to identify concrete ways for its further improvement. This research phase was conducted within three universities: Borys Grinchenko Kyiv University in Ukraine, Constantine the Philosopher University in Nitra, Slovak Republic and Herzen State Pedagogical University of Russia. The Research instrument contains three sections (dimensions): characteristic of Open University resources; the questionnaire, detecting students' information behaviour and attitude towards different networking activities in university information environment; global ranking of university internet integration. The study shows that the proposed set of indicators allows to determine the overall level of university virtual learning environment development and to identify specific areas for its improvement. For a more complete study of the university virtual environment, the developed set of tools must be supplemented by internal indicators reflecting e-learning methodology, achieved educational outcomes, etc. But it is the task of the next phase of the study.